Role of the main effector cells of the innate immune system in the development of meta-inflammation of adipose tissue in obesity - A.E. Abaturov; A.А. Nikulina (Zaslavsky O.Yu., 2020)
The literature review presents modern data on the role of the main effector cells of the innate immune system (macrophages, neutrophils, monocytic cells) in the development of obesity. According to the modern concept, obesity is considered as a disease proceeding with the development of a chronic inflammatory reaction with a low level of activity, which is called meta-inflammation. The molecular features of overweight-induced meta-inflammation are of particular practical interest in the context of an obesity pandemic in the human population. The development of obesity is accompanied by an increase in the level of free fatty acids in adipose tissue. Free fatty acids, interacting with TLR4 and TLR2 of adipocytes, activate the signaling pathways NF-κB and MAPK8, which leads to the production of pro-inflammatory cytokines and chemokines. The inflammatory response in obesity as a result of excessive accumulation of fat in adipocytes is characterized by a change in the spectrum of products synthesized by them: a decrease in the level of secretion of adiponectin, IL-10, TGF-β; increased synthesis of resistin, leptin, CCL2, IL-6, TNF-α. These changes in the spectrum of synthesized adipokines and cytokines, which affect adipose tissue over a relatively long period of time, lead to the recruitment of various immunocytes into metabolically active regions of adipose tissue and impairment of adipogenesis. The data are provided on the differences in the pathophysiological processes of the formation of meta-inflammation in the subcutaneous and visceral adipose tissues characterized by features both in the level of recruited immunocytes and in the mechanisms of clearance of inflamed and hypertrophied adipocytes. In the subcutaneous adipose tissue, hypertrophy is predominantly observed, and in the visceral adipose tissue - hypertrophy and hyperplasia of adipocytes, which to a large extent determines the formation of a complicated course of obesity and insulin resistance. Isolation of the key pro-inflammatory factors associated with obesity will make it possible to find new therapeutic approaches to the prevention and treatment of metabolic disorders that threaten the health and life of patients.